2021
DOI: 10.1001/jamaophthalmol.2021.0349
|View full text |Cite
|
Sign up to set email alerts
|

MOG-IgG Among Participants in the Pediatric Optic Neuritis Prospective Outcomes Study

Abstract: Myelin oligodendrocyte glycoprotein (MOG) immunoglobulin G (IgG)-associated disorder (MOGAD) is a recently described entity that is distinct from multiple sclerosis (MS) and aquaporin-4 (AQP4)-IgG-positive neuromyelitis optica spectrum disorder. 1-3 A small cohort from the Pediatric Optic Neuritis Prospective Outcomes Study 4 underwent MOG-IgG testing and we compared those whose results were MOG-IgG positive with those whose results were negative.Methods | The study, protocol, and Health Insurance Portability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“… 31 Two studies reported median visual acuity of 1.0, one with an IQR of 1.0, 1.0 70 and one with a range of 0.8–1.0. 62 The logMAR was reported by three studies: one with median 0.0 (IQR 0.0, 1.0), 72 one with median 0.1, 71 and one with logMAR 0.0 in 73% of patients. 73 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 31 Two studies reported median visual acuity of 1.0, one with an IQR of 1.0, 1.0 70 and one with a range of 0.8–1.0. 62 The logMAR was reported by three studies: one with median 0.0 (IQR 0.0, 1.0), 72 one with median 0.1, 71 and one with logMAR 0.0 in 73% of patients. 73 …”
Section: Resultsmentioning
confidence: 99%
“…Conversely, one study of 10 patients reported a median visual acuity of 1.0 (interquartile range (IQR) 0.2, 1.0) using the decimal scale 70 . Two studies reported the median logarithm of the minimal angle of resolution (logMAR) to be 1.7 71,72 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 This longitudinal data collection study was the first large multicenter one on this topic and has produced valuable information regarding visual outcomes and distribution of pediatric optic neuritis subtypes. [2][3][4] Claire Sheldon coordinated a multicenter study of anthropometrics in children with pediatric idiopathic intracranial hypertension (IIH). Her group found that there are 3 subgroups of pediatric IIH, compared with age and gender norms: 1) a population (younger than 8 years) with normal body mass index, 2) an early adolescent group that is either overweight or obese and tall, and 3) a late adolescent group that is mostly obese.…”
mentioning
confidence: 99%